THE OVERLAPPING OF REGULATIONS ON MARINE RESOURCES LAW ENFORCEMENT AND CUSTOMARY LAW AS AN ALTERNATIVE TO CONFLICT SETTLEMENT IN THE KEI ISLANDS - Andreas M. D Ratuanak; Ratih Lestarini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research is socio-legal research with an ethnographic approach regarding the resolution of maritime resource conflicts in the Kei Islands and the conditions of current state laws and regulations. This article discusses how the overlapping of laws and regulations occurs in law enforcement on marine resource management and how customary law is an alternative for resolving conflicts over marine resources in the Kei Islands. This study found that so many laws and regulations besides helping to create legal order can also have an impact in the form of overlapping authorities between state agencies. On the other hand, the resolution of maritime resource conflicts in practice does not always depend on the positive law of the state alone. Another fact is often found that the community and even the state apparatus also accommodate customary law in resolving conflicts that occur. However, this form of settlement developed into a hybrid form.Keywords: the overlapping regulations, Kei customary law, hybrid legal systems.